UPAYA PEMENUHAN KEBUTUHAN ISTIRAHAT TIDUR PADA IBU POSTPARTUM DENGAN PREEKLAMPSIA - Pinky Novitasari; Heny Prasetyorini; Dyah Restuning Prihati (Universitas Widya Husada Semarang, 2018)
All new-born mothers suffer from postpartum fatigue on average, especially in the early period, as a result the mother lacks sleep plus the responsibility that must be given to her baby. The first three days after giving birth are usually difficult for the mother to rest. Attempts to fulfill sleep restriction have created a comfortable atmosphere, reduced environmental distraction and sleep disturbances, limited visitors during client breaks, assessed fatigue, duration and type of labor, examined factors affecting rest, provided information about the need to sleep or rest after returning to home, study the home environment, help at home and other family members. The purpose of this study is to fulfill and maintain sleep rest in postpartum mothers who can provide enough energy to undergo daily activities. The method used by the author is observation, interview, measurement, and documentation. The subjects in this case study were two postpartum patients with normal second-day postpartum criteria, postpartum with preeclampsia, postpartum mothers with healthy infants. The results of the analysis conducted by the authors found problems with sleep patterns. The results of the study show that the nursing problems of sleep pattern disorders have not been resolved because the results of the PSQI questionnaire in the sleep quality of the two respondents were still poor. Recommendations need to continue to provide support and motivation to get enough rest, and encourage to increase the intensity of rest and sleep.